Towards the mechanism of the accelerated corrosion of decorative nickel–chromium coatings in the presence of metals and their salts. Issue 10 (12th September 2013) - Schmidt, R.; Thiel, K.‐O.; von Horsten, F.; Spickermann, C.; Vazhenin, G.; Bäulke, N.; Wachter, P.; Hartmann, P.; Schreier, H.‐J.
<x xml:space="preserve">Abstract</x> Microscopic studies suggested accelerated nickel corrosion to account for the extensive failure of decorative nickel chromium coatings. Electrochemical experiments further confirmed the crucial role of chloride, cupric, and ferric ion containing salts, which were found before on the corroded surface. Density functional theory calculations were used in the following to explain experimental observations and to obtain a detailed understanding of the mechanism of the accelerated corrosion under specific corrosive environments on the molecular level. The results of the calculations were discussed taking into account literature known models for pitting corrosion.